Multiply and simplify:

6xy3z • 3x2yx2

Answers

The answer was wrong . The correct answer is 18x^5y^4z

The product of 6xy^3z and 3x^2yx^2  is 18x^5y^4z

Step-by-step explanation:

Consider the given expression, 6xy^3z and 3x^2yx^2    

We have to multiply the above two expressions.

we first simplify the second expression 3x^2yx^2=3x^4y    

Consider the product,  6xy^3z \cdot 3x^2yx^2

6xy^3z \cdot 3x^4y

Using x^n\cdot x^m=x^{n+m} , We get ,

6xy^3z \cdot 3x^4y=18x^5y^4z

Thus, the product of 6xy^3z and 3x^2yx^2  is 18x^5y^4z

1) 2y^{2}+4y-9

2) 18x^{5}y^{4}z

3) 6x^{5}-12x^{4}+9x^{3}

4) 40

5) x^{3}-7x^{2}+3x+36


Step-by-step explanation:

1) Distribute the negative sign that is outside the parentheses and then you must add like terms, as following:

(y^{2}-3y-5)-(-y^{2}-7y+4)=y^{2}-3y-5+y^{2}+7y-4=2y^{2}+4y-9

2) According to the Product property of exponents, when you multiply powers with the same base, you must add the exponents. Then:

(6xy^{3}z)(3x^{2}yx^{2})=18x^{5}y^{4}z

3) Apply the Distributive property and the Product property of exponents. Then, you obtain:

-3x^{3}(-2x^{2}+4x-3)=6x^{5}-12x^{4}+9x^{3}

4) (4a+5)^{2} is a square of a sum, then, by definition you have:

(a+b)^{2}=a^{2}+2ab+b^{2}

Then:

(4a+5)^{2}=(4a)^{2}+2(4a)(5)+5^{2}=16a^{2}+40a+25

The coefficient of the second term is the number in front of the variable a. Then, the answer is: 40

5)  Apply the Distributive property and the Product property of exponents, then, oyou must add the like terms:

(x-4)(x^{2}-3x-9)=x^{3}-3x^{2}-9x-4x^{2}+12x+36=x^{3}-7x^{2}+3x+36

1. y^2 - 3y - 5 - (-y^2 - 7y + 4) = y^2 - 3y - 5 + y^2 + 7y - 4 =
    2y^2 + 4y - 9 <===

2. 6xy^3z * 3x^2yx^2 = 18x^5y^4z

3. -3x^3(-2x^2 + 4x - 3) = 6x^5 - 12x^4 + 9x^3

4. (6p + 2)^2 = (6p + 2)(6p + 2) = 36p^2 + 12p + 12p + 4 = 
    36p^2 + 24p + 4coefficient is 24

5. (x - 5)(x^2 - 2x - 6) = x(x^2 - 2x - 6) - 5(x^2 - 2x - 6) =
     x^3 - 2x^2 - 6x - 5x^2 + 10x + 30 =
     x^3 - 7x^2 + 4x + 30 <===

18x^{5}y^{4}z

Step-by-step explanation:

we have

(6xy^{3}z)(3x^{2} yx^{2})

Group terms that contain the same variable

(6*3)(x*x^{2}*x^{2})(y^{3}*y)(z)

Using

x^a\cdot x^b=x^{a+b}

(18)(x^{1+2+2})(y^{3+1})(z)

(18)(x^{5})(y^{4})(z)

18x^{5}y^{4}z

The simplified answer is 18x5y4z.


Do you know the answer?

Other questions on the subject: Mathematics

m = 1575Step-by-step explanation:so first you have to simplify the equation: m = 45 (35) because the absolute value of -35 is 35. after that you multiply 45 by 35 and end up with 1...Read More
2 more answers
Mathematics, 21.06.2019, cr22estiles
dilation scale factor 2: starting with δabc, draw the dilation image of the triangle with a center at the origin and a scale factor of two. notice that every coordinate of the ori...Read More
2 more answers
Mathematics, 21.06.2019, aleilyg2005
1) PN, MP, MN (15, 75, 90, then angle side inequality)2)10<x<223) SR, TR, ST(x=17, R=93, S=57, T=30, angle side inequality)4)14,14,7 (cant be 7,7,14 because 7+7=14 so it wont...Read More
1 more answers
1. Angle-Side-Angle (ASA) Postulate2. Corresponding parts of congruent triangles are congruent (CPCTC)Step-by-step explanation:Given : ABC is a triangle,In which, ∠BAC ≅ ∠BCA To p...Read More
3 more answers
Mathematics, 21.06.2019, monij4
“a term can be a signed number, a variable, or a constant multiplied by a + sign or j sign. in , the terms are 5x , 3y and 8. when a term is made up of a constant multiplied by a v...Read More
1 more answers